Diversity in Antistaphylococcal Mechanisms among Membrane-Targeting Antimicrobial Peptides - Koo, Su-Pin (American Society for Microbiology, 2001)
Many antimicrobial peptides permeabilize the bacterial cytoplasmic membrane. However, it is unclear how membrane permeabilization and antimicrobial activity are related for distinct peptides. This study investigated the relationship between Staphylococcus aureus membrane permeabilization and cell death due to the following antistaphylococcal peptides: thrombin-induced platelet microbicidal protein 1 (tPMP-1), gramicidin D, and protamine. Isogenic S. aureus strains ISP479C and ISP479R (tPMP-1 susceptible and resistant, respectively), were loaded with the fluorochrome calcein and exposed to a range of concentrations of each peptide. Flow cytometry was then used to monitor membrane permeabilization by quantifying the release of preloaded calcein. Killing was determined by quantitative culture at time points simultaneous to measurement of membrane permeabilization. Membrane permeabilization and killing caused by tPMP-1 occurred in a time- and concentration-dependent manner, reflecting the intrinsic tPMP-1 susceptibilities of ISP479C and ISP479R. In comparison, gramicidin D killed both S. aureus strains to equivalent extents in a concentration-dependent manner between 0.5 to 50 μg/ml, but cell permeabilization only occurred at the higher peptide concentrations (25 and 50 μg/ml). Protamine permeabilized, but did not kill, either strain at concentrations up to 10 mg/ml. Regression analyses revealed different relationships between membrane permeabilization and staphylocidal activity for the distinct antimicrobial peptides. Taken together, these findings demonstrate that permeabilization, per se, does not invariably result in staphylococcal death due to distinct antimicrobial peptides. Thus, although each of these peptides interacts with the S. aureus cytoplasmic membrane, diversity exists in their mechanisms of action with respect to the relationship between membrane permeabilization and staphylocidal activity.